2000
DOI: 10.1152/ajpregu.2000.278.4.r995
|View full text |Cite
|
Sign up to set email alerts
|

Medullary lateral tegmental field: an important source of basal sympathetic nerve discharge in the cat

Abstract: We used blockade of excitatory amino acid (EAA) neurotransmission in the medullary lateral tegmental field (LTF) and rostral ventrolateral medulla (RVLM) to assess the roles of these regions in the control of inferior cardiac sympathetic nerve discharge (SND) and mean arterial pressure (MAP) in urethan-anesthetized, baroreceptor-denervated cats. Bilateral microinjection of a non-N-methyl-D-aspartate (NMDA)-receptor antagonist [1,2,3, 4-tetrahydro-6-nitro-2,3-dioxobenzo-[f]quinoxaline-7-sulfonamide (NBQX)] into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
52
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 39 publications
12
52
0
Order By: Relevance
“…In the current study, chemical inactivation of the LTF reduced total power in the 0-to 5-Hz band of SND to 75% of control. Moreover, our past work (10,45) showed that SND was reduced to ϳ50% of control after blockade of non-NMDA receptor-mediated transmission in the LTF of baroreceptor-innervated and -denervated cats. These observations support the view that the LTF plays an important role in setting the level of basal SND, at least in the cat.…”
Section: Ltf and Vagal Lung Inflation Afferentsmentioning
confidence: 97%
See 3 more Smart Citations
“…In the current study, chemical inactivation of the LTF reduced total power in the 0-to 5-Hz band of SND to 75% of control. Moreover, our past work (10,45) showed that SND was reduced to ϳ50% of control after blockade of non-NMDA receptor-mediated transmission in the LTF of baroreceptor-innervated and -denervated cats. These observations support the view that the LTF plays an important role in setting the level of basal SND, at least in the cat.…”
Section: Ltf and Vagal Lung Inflation Afferentsmentioning
confidence: 97%
“…2, 6, and 8), the data block beginning 10 min after microinjection was used to quantify the effects of chemical inactivation of the LTF on the interrelationships of ITP, SND, and PNA. This time point was chosen because our past work showed that the maximum changes in basal SND had occurred at this time, and SND had reached a new steady-state level (9,10,45).…”
Section: Microinjectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures used for exposing the brain stem and for microinjection of drugs into the LTF are the same as those described in earlier reports from this laboratory (4,26,27,29). In fact, the cats in which we studied the effects of muscimol microinjection into the LTF on the Bezold-Jarisch reflex were also included in the study of the effects of chemical inactivation of the LTF on the influence of vagal lung inflation afferents on SND and PNA (29).…”
Section: Microinjectionsmentioning
confidence: 99%